2022
DOI: 10.2166/wcc.2022.410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of satellite-based and reanalysis precipitation datasets by hydrologic simulation in the Chenab river basin

Abstract: Several satellite-based and reanalysis products with a high spatial and temporal resolution have become available in recent decades, making it worthwhile to study the performance of multiple precipitation forcing data on hydrological modeling. This study aims to examine the veracity of five precipitation products employing a semi-distributed hydrological model, i.e., the Soil and Water Assessment Tool (SWAT) to simulate streamflow over the Chenab River Basin (CRB). The performance indices such as coefficient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 99 publications
0
2
1
Order By: Relevance
“…The ERA5-Land precipitation dataset had inappropriate accuracy in estimating minimum discharges and overestimated them. Although the results of this study indicate that the PERSIANN-CDR dataset performs better than ERA5-Land in simulating runoff on monthly and daily scales, although the findings of Ougahi et al (2022) [81] contradict these results. However, the modeling results of Usman et al (2022) [82] showed that the accuracy of simulating runoff using both the APHRODITE and PERSIANN-CDR datasets was comparable and better than ERA5-Land, which is consistent with the findings of this study.…”
Section: Monthly Results Evaluationcontrasting
confidence: 75%
“…The ERA5-Land precipitation dataset had inappropriate accuracy in estimating minimum discharges and overestimated them. Although the results of this study indicate that the PERSIANN-CDR dataset performs better than ERA5-Land in simulating runoff on monthly and daily scales, although the findings of Ougahi et al (2022) [81] contradict these results. However, the modeling results of Usman et al (2022) [82] showed that the accuracy of simulating runoff using both the APHRODITE and PERSIANN-CDR datasets was comparable and better than ERA5-Land, which is consistent with the findings of this study.…”
Section: Monthly Results Evaluationcontrasting
confidence: 75%
“…The dataset was preferred over other reanalyses for its high spatial resolution (0.25 o × 0.25 o ) and temporal resolution. Some recent studies have compared the performance of ERA5 against other reanalysis products and have shown that ERA5 is highly reliable for hydrological applications including the study of extremes (Bhattacharyya et al, 2022;Mahto and Mishra, 2019;Ougahi and Mahmood, 2022).…”
Section: Study Area and Datamentioning
confidence: 99%
“…This creates problems for monitoring or forecasting the risk of hydrometeorological hazards like flooding and landslides [19]. However, remote sensing and reanalysis precipitation datasets hold significance in these regions where data availability is limited [20]. Precipitation stands as the primary contributor to uncertainty which leads to varying optimal ranges for the fine-tuned parameters [21].…”
Section: Introductionmentioning
confidence: 99%